2006
DOI: 10.1369/jhc.5a6905.2006
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Characterization of Elastic System Fibers in Rat Molar Periodontal Ligament

Abstract: S U M M A R Y Among elastic system fibers, oxytalan fibers are known as a ubiquitous component of the periodontal ligament, but the localization and role of elastin-containing fibers, i.e., elastic and elaunin fibers, has yet to be clarified. In this study, we immunohistochemically investigated the localization of elastin and fibrillin, major proteins of elastin-containing fibers in the periodontal ligament of rat lower first molars. At the light microscope level, distribution of elastin-positive fibers was no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 21 publications
4
22
0
2
Order By: Relevance
“…However, the importance of the molecular mechanisms governing fibrillin-1 assembly during organogenesis has been hampered by the unanswered issue of the actual factor that drives microfibril assembly. Our present study demonstrates that ADAMTSL6␤, an inducing factor for microfibril assembly (18), regulates development and regeneration of PDL. Furthermore, ADAMTSL6␤-mediated fibrillin-1 microfibril assembly may accelerate the sequestration of large latent complexes of TGF-␤ or active TGF-␤, thereby negatively regulating the expression of TGF-␤ regulatory targets, such as periostin (35,42).…”
Section: Discussionsupporting
confidence: 59%
“…However, the importance of the molecular mechanisms governing fibrillin-1 assembly during organogenesis has been hampered by the unanswered issue of the actual factor that drives microfibril assembly. Our present study demonstrates that ADAMTSL6␤, an inducing factor for microfibril assembly (18), regulates development and regeneration of PDL. Furthermore, ADAMTSL6␤-mediated fibrillin-1 microfibril assembly may accelerate the sequestration of large latent complexes of TGF-␤ or active TGF-␤, thereby negatively regulating the expression of TGF-␤ regulatory targets, such as periostin (35,42).…”
Section: Discussionsupporting
confidence: 59%
“…This concurs with the findings of Kajikawa et al;Cotta-Pereira et al (1976) and Sawada et al (2006), the elaunin fibers, in turn, are ultrastructurally characterized by being composed of scarce amorphous material scattered amid the microtubular component, as previously shown by CottaPereira et al (1976CottaPereira et al ( , 1977. However, the oxytalan fibers are represented by bundles of microtubules arranged in parallel, confirming the findings of Simmons & Avery (1980), De Carvalho & Line (1996, Chopard et al (1998) and Chopard & Gerhard (2000).…”
Section: Discussionsupporting
confidence: 92%
“…This was also shown by in vitro studies that cultured gingival fibroblasts expressed both microfibrils and elastin (Tsuruga et al, 2002a), and PDL-cells only expressed microfibrils, fibrillin-1 and fibrillin-2 (Tsuruga et al, 2002b). The immunolocalization of elastin and fibrillins in the rat PDL is reported (Sawada et al, 2006). It is shown that a small amount of elastin is localized in the apical region of the PDL.…”
Section: Marfan Syndrome and Its Disorder In Periodontal Tissuesmentioning
confidence: 63%